1994
DOI: 10.1073/pnas.91.17.8117
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in substantia nigra following developmental striatal excitotoxic injury.

Abstract: We have previously observed that an axon-sparing injury to the developing striatum induced by the excitotoxin quinolinate results in a decrease in dopaminergic neurons in the substantia nigra pars compacta (SNpc) of the adult. This decrease occurs in the absence of direct injury to the SNpc. As the striatum is a major target for the SNpc dopaminergic system, we have hypothesized that a decrease in the size of the striatal target during development may result in an induced regressive event in the SNpc, similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
114
3

Year Published

1996
1996
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(129 citation statements)
references
References 26 publications
12
114
3
Order By: Relevance
“…3A). This appearance of chromatin clumps on silver stain has been shown to correspond to electron-dense chromatin clumps, characteristic of apoptosis, on ultrastructural study of apoptotic dopaminergic neurons of the SN (Macaya et al, 1994). The apoptotic nature of this morphological pattern of cell death was confirmed further by histochemical demonstration of abundant free 3Ј ends, in the nucleus of the nigral cells in association with basophilic chromatin clumps, again demonstrated by Nissl counterstain (Fig.…”
Section: Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…3A). This appearance of chromatin clumps on silver stain has been shown to correspond to electron-dense chromatin clumps, characteristic of apoptosis, on ultrastructural study of apoptotic dopaminergic neurons of the SN (Macaya et al, 1994). The apoptotic nature of this morphological pattern of cell death was confirmed further by histochemical demonstration of abundant free 3Ј ends, in the nucleus of the nigral cells in association with basophilic chromatin clumps, again demonstrated by Nissl counterstain (Fig.…”
Section: Resultsmentioning
confidence: 61%
“…The demonstration of intensely basophilic, rounded, and well demarcated chromatin clumps using Nissl stains has been considered by many investigators to be highly suggestive of apoptosis at the light microscope level (Clarke and Oppenheim, 1995), and in many instances this has been confirmed by ultrastructure (Cunningham, 1982;Williams and Rakic, 1988;Ferrer et al, 1990;Sloviter et al, 1993;Macaya et al, 1994). The apoptotic nature of such clumps can be confirmed by silver impregnation techniques, which demonstrate intensely argyrophilic, rounded intranuclear clumps (Yamamoto et al, 1986;Janec and Burke, 1993;Macaya et al, 1994;Mitchell et al, 1994), and which have also been demonstrated by ultrastructure (Macaya et al, 1994) to conform to classic descriptions of apoptosis (Kerr et al, 1995). In addition, we have shown that apoptosis occurs by demonstrating a high concentration of free 3Ј ends within the nucleus in the presence of basophilic chromatin clumps, visualized with Nissl counterstain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations